In Situ Reactive Assembly of Scalable Core–Shell Sulfur–MnO2 Composite Cathodes - Liang, Xiao; Nazar, Linda F (ACS nano, 2016)
The lithium–sulfur battery is the subject of much recent attention, but the polysulfide shuttle remains problematic owing to dissolution of intermediate polysulfide species in the electrolyte. Despite much effort in limiting such dissolution via physical confinement or chemical binding to the sulfur host materials, the high cost and complicated preparation of the related materials present an impediment to their practical application. Here we demonstrate a simple methodology to fabricate an effective nanometric MnO2 shell on sulfur particles, which is realized by an in situ redox reaction between sulfur and KMnO4 under ambient conditions. The bifunctional MnO2 shell provides physical confinement and chemical interaction and shows excellent efficiency for trapping the polysulfides. MnO2 sheets crystallized onto nanosized sulfur particles result in cathodes with a very low fading rate of 0.039% per cycle over 1700 cycles in Li–S cells. Moreover, directly crystallizing nanometric shells of MnO2 on micrometer-sized sublimed sulfur delivers stable Li–S cycling performance over 800 cycles. Since both sulfur and KMnO4 are inexpensive and widely used, the production of MnO2-coated sulfur composites can be easily scaled-up for practical applications of Li–S batteries in light of the very simple reaction processes involved.